Tomato seeds vigor under water or salt stress - Silva Júnior, Josué Ferreira [UNESP] (2014)
The aim of this study was to evaluate the water and salt stress in the germination process of two tomatoes cultivars. The experiment consisted of 16 treatments in a completely randomized design in triple 2 x 2 x 4 factorial design, with two tomatoes cultivars (Santa Adélia and Kátia), two imbibition solutions (PEG6000 and NaCl) and four osmotic potentials (0, -0.2, -0.4 and -0.6 MPa). Each plot was represented by a gerbox with 50 tomatoes seeds. The seeds were remained in contact with the solutions for fourteen days. The germination percentage, emergence rate index, length and dry weight of the seedlings were evaluated. Significant interactions between the factors were deployed. Qualitative factors underwent comparison of means by Tukey test (P < 0.05) and the quantitative analysis by linear regression. According to the results of the study, Santa Adélia cultivar was the most resistant for both situations, hydric and salt stress. The hydric stress was significantly more effective in reducing the results for each variable, except for dry mass. The osmotic potential, from -0.4 Mpa, significantly reduced the germination percentage, index emergency speed and seedlings.